Types of Idiom and Their Meaning in Michael Jackson “Thriller” Album - I Kadek Adi Sukrawan; Ni Made Verayanti Utami; I Gusti Agung Sri Rwa Jayantini (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2021)
This study is entitled “The Types of Idiom and Their Meaning in Michael Jackson “Thriller” Album”. The data in this study is taken from one of Michael Jackson album entitle “Thriller”. This study is analyzed about types of idiom including the types of meaning and their meaning. This study is chosen because the meaning of a idiom in a sentence sometimes cannot be translated directly and need to be further intellectuality to caught its real meaning. There are two theories that used in this study the first one is the theory about the types of idiom form Frank Robert Palmer that is taken from his book entitled “Semantic: a new outline (1976) ” as the main theory for the second theory is taken from Geofery Leech about the types of meaning on his book entitled “Semantic the study of meaning(1974)”. The result of analyze in this study there were found 9 types of idiom in this album, they were 4 types of partial idiom (44, 44%) and 5 types of total idiom (55, 56). for the types of meaning there were found 9 types of meaning, they were 4 connotative meaning (44, 44%) and 5 affected meaning (55, 56%) .